Electroacupuncture and Cognitive Behavioural Therapy for Sub-Syndromal Depression among Undergraduates: A Controlled Clinical Trial. Issue 5 (October 2016) - Guo, Tianwei; Guo, Zhuo; Zhang, Wenyue; Ma, Wenhao; Yang, Xinjing; Yang, Xueqin; Hwang, Jiwon; He, Xiaotian; Chen, Xinyi; Ya, Tu
Background: Individuals with sub-syndromal depression (SSD) are at increased risk of incident depressive disorders; however, the ideal therapeutic approach to SSD remains unknown. Objective: To evaluate the effects of electroacupuncture (EA) and cognitive behavioural therapy (CBT), alone or in combination, on depressive symptoms. Methods: Undergraduate students with SSD were recruited and allocated to one of four groups based on their preferences: EA (n=6), CBT (n=10), EA+CBT (n=6), and untreated control (n=11) groups. Six weeks of treatment were provided in the first three groups. Clinical outcomes were measured using the 17-item Hamilton Depression (HAMD-17) rating scale, Center for Epidemiologic Depression (CES-D) scale, WHO Quality of Life-Brief version (WHOQOL-BREF) questionnaire, and clinical remission rate. Results: All 33 subjects were included in an intent-to-treat analysis. Statistically significant improvements in HAMD-17, CES-D, and WHOQOL-BREF scores and a higher remission rate were found in the EA, CBT, and EA+CBT intervention groups compared with the control group (all p<0.05). No significant differences were found between the three intervention groups. HAMD-17 factor score analysis revealed that EA reduced sleep disturbance scores more than CBT or EA+CBT (p<0.05), and CBT reduced retardation scores more than EA (p<0.01). EA+CBT reduced anxiety/somatisation scores more than EA or CBT (p<0.05) and retardation scores more than EA (p<0.05). Conclusions: Early intervention may alleviate depressive symptoms in SSD. EA and CBT may have differential effects on certain symptoms. Combination therapy targeting both physical and psychological symptoms may represent an ideal strategy for SSD intervention. However, randomised trials with larger sample sizes are needed. Trial Registration Number: ChiCTR-TRC-10000889; Results.